European Lung Foundation: from local to global. Issue 3 (September 2016) - Powell, Pippa; Williams, Sîan; Smyth, Dan
Key points: Although there are many patient organisations in Europe, this is not the case in all countries across the globe. Access to care is one of the main global issues highlighted by the European Lung Foundation International Patient Advisory Committee. The European Respiratory Society/European Lung Foundation Healthy Lungs for Life campaign can be used locally or globally to raise awareness of the risk factors for lung disease. Implementation science is a method that can be used to assess the feasibility of using research findings in routine healthcare in clinical settings in different parts of the world. Educational aims: To show how patient- and public-focussed initiatives and activities can be adapted and modified to be effective in local, national and international settings, and to provide specific examples of these from the European Lung Foundation. Read about ELF's local to global actions in this edition of Breathe http://ow.ly/SQ3d301Py5q